2020
DOI: 10.3892/ijo.2020.4984
|View full text |Cite
|
Sign up to set email alerts
|

miR‑21 inhibits autophagy and promotes malignant development in the bladder cancer T24�cell line

Abstract: is reported to exhibit cancer-promoting activity in various types of cancer. It has been previously demonstrated that miR-21 is overexpressed in bladder tumor tissue compared with normal mucosa. However, the functional mechanism of miR-21 in bladder cancer remains largely unknown. Thus, the current study aimed to determine the roles of miR-21 in autophagy and the malignant development of bladder cancer in T24 cells. Upregulation or downregulation of miR-21 was achieved following the transfection of miR-21 mimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 33 publications
(34 reference statements)
0
13
0
Order By: Relevance
“…miRNAs also regulates mTOR induced autophagy progress. In BC this process is inhibited by miR-21 which inhibits PTEN, caspase-3, beclin-1 and E-cadherin causing cell proliferation, invasion and migration as well as inhibition of apoptosis [ 75 ]. Wang et al reported the autophagy promoting role of sodium butyrate (NaB) in BC.…”
Section: Mirna-mediated Regulation Of Mtor In Bladder Cancermentioning
confidence: 99%
“…miRNAs also regulates mTOR induced autophagy progress. In BC this process is inhibited by miR-21 which inhibits PTEN, caspase-3, beclin-1 and E-cadherin causing cell proliferation, invasion and migration as well as inhibition of apoptosis [ 75 ]. Wang et al reported the autophagy promoting role of sodium butyrate (NaB) in BC.…”
Section: Mirna-mediated Regulation Of Mtor In Bladder Cancermentioning
confidence: 99%
“…Zhang et al . 66 found that miR-21 exhibited a tumor promotion effect through autophagy inhibition. They observed autophagy inhibition and increased tumor properties in T24 bladder cancer cells transfected with miR-21 mimics.…”
Section: Cell Death Effects Of Autophagy On Bladder Cancer Cellsmentioning
confidence: 99%
“…It has dual functions with both cancer‐suppressing and cancer‐promoting factors 43 . However, studies have revealed that autophagy is usually constitutively activated and is correlated with malignant BC tumor development 44 . A high basal level of autophagy in BC affects the therapeutic effect by increasing the cell survival rate, inhibiting apoptotic cell death, and eventually contributing to resistance to anticancer treatment 45 .…”
Section: Discussionmentioning
confidence: 99%